ANALISIS PENERAPAN TARIF EFEKTIF RATA-RATA (TER) TERHADAP PEMOTONGAN PAJAK PENGHASILAN PASAL 21 KARYAWAN TETAP (STUDI KASUS PADA PT CDS) - hanifah hanifah; Nor Hayati (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2024)
The purpose of this study is to determine the impact of the implementation of the Average Effective Rate (TER) on the withholding of income tax article 21 of permanent employees at PT. CDS. The method used in this study is qualitative descriptive, with this method the author can find out the extent of the income tax withholding article 21 of PT. CDS before and after the implementation of the Average Effective Rate (TER). The results of this study show that after using the Average Effective Rate (TER) from January to June 2024, PT. CDS made a deduction of IDR 5,369,000, but the use of the Average Effective Rate (TER) can cause overpayment of taxes.